Pembelajaran Bahasa Arab Sebagai Bahasa Kedua Pada Siswa Dalam Aplikasi Teori Kontruktivisme - Nur, Muhammaf Fahrudin; Zaeni, Rahmania Auriel; Hilmi, Danial; Basid, Abdul (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
ملخص: تعتبر نظرية البنائية التي طرحها بياجيه التطور المعرفي عملية اكتشاف يقوم بها الفرد بشكل مستقل، حيث يُتوقع من المتعلمين بناء معارفهم الخاصة من خلال التجربة والتفاعل مع البيئة. تتأثر هذه العملية بنضوج الجهاز العصبي الذي يصبح أكثر تعقيداً مع تقدم العمر، مما يؤدي إلى تعزيز القدرات الفكرية للفرد. يجب تكييف التعلم مع مراحل التطور المعرفي، بما في ذلك تعلم اللغة العربية كلغة ثانية. تهدف هذه الدراسة إلى وصف تطبيق نظرية البنائية في تعلم اللغة العربية مع التركيز على تعديل استراتيجيات التدريس بما يتناسب مع القدرات الفكرية للطلاب. تشير نتائج الدراسة إلى أن تطبيق نظرية البنائية ذو صلة كبيرة، لأنه يشجع الطلاب على بناء معارفهم من خلال التجارب والتفاعلات مع بيئتهم. في الختام، يساهم تطبيق نظرية البنائية بشكل كبير في تعلم اللغة العربية، مع التأكيد على أهمية تعديل استراتيجيات التدريس بما يتناسب مع مراحل التطور المعرفي للطلاب. الكلمات الرئيسية: نظرية البنائية، تعلم اللغة العربية، اللغة الثانية، بياجيه. Abstracts: The constructivist theory proposed by Piaget views cognitive development as a process of discovery carried out by individuals independently, where learners are expected to build their own knowledge through experience and interaction with the environment. This process is influenced by the maturation of the nervous system, which becomes increasingly complex as age increases, leading to the enhancement of an individual's intellectual abilities. Learning must be adapted to the stages of cognitive development, including in Arabic language learning as a second language. This study aims to describe the application of constructivist theory in Arabic language learning, focusing on adjusting teaching strategies according to students' intellectual abilities. The results of the study indicate that the application of constructivist theory is highly relevant, as it encourages students to construct their knowledge through experiences and interactions with their surroundings. In conclusion, the implementation of constructivist theory makes a significant contribution to Arabic language learning, emphasizing the importance of adjusting teaching strategies according to students' cognitive development stages. Keywords: Constructivist theory, cognitive development, Arabic language learning, second language, Piaget. Abstrak: Teori konstruktivisme yang dikemukakan oleh Piaget memandang perkembangan kognitif sebagai proses penemuan yang dilakukan oleh individu secara mandiri, di mana pelajar diharapkan dapat membangun pengetahuan mereka sendiri melalui pengalaman dan interaksi dengan lingkungan. Proses ini dipengaruhi oleh kematangan sistem saraf yang semakin kompleks seiring bertambahnya usia, yang berdampak pada peningkatan kemampuan intelektual individu. Pembelajaran harus disesuaikan dengan tahapan perkembangan kognitif, termasuk dalam pembelajaran Bahasa Arab sebagai bahasa kedua. Penelitian ini bertujuan untuk mendeskripsikan penerapan teori konstruktivisme dalam pembelajaran Bahasa Arab dengan fokus pada penyesuaian strategi pembelajaran sesuai dengan kemampuan intelektual siswa. Hasil penelitian menunjukkan bahwa penerapan teori konstruktivisme sangat relevan, karena dapat mendorong siswa untuk membangun pengetahuan mereka melalui pengalaman dan interaksi dengan lingkungan sekitar. Kesimpulannya, penerapan teori konstruktivisme memberikan kontribusi signifikan dalam pembelajaran Bahasa Arab, dengan menekankan pentingnya penyesuaian strategi pengajaran sesuai dengan tahap perkembangan kognitif siswa. Kata kunci: Teori konstruktivisme, perkembangan kognitif, pembelajaran Bahasa Arab, bahasa kedua, Piaget Kata kunci: Teori konstruktivisme, perkembangan kognitif, pembelajaran Bahasa Arab, bahasa kedua, Piaget